2001
DOI: 10.1017/s1041610201007475
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Efficacy and Safety of Low-Dose Sertraline and Standard-Dose Imipramine for the Treatment of Depression in Older Adults: Results From a Double-Blind, Randomized, Controlled Clinical Trial

Abstract: This study compared the efficacy and tolerability of 150 mg/day imipramine and 50 mg/day sertraline for the treatment of a major depressive episode (DSM-IV) in older adults (N = 55) in an 8-week, randomized, double-blind, controlled clinical trial. Intention-to-treat analysis (last observation carried forwards) showed a reduction of 50% or more on the baseline scores of the Montgomery-Åsberg Rating Scale (MADRS) in 60.7% and 55.6% of patients receiving imipramine and sertraline, respectively (p = .698). Full r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…This study aimed to examine remission based on a categorical MADRS score less than ten. Other studies have used MADRS scores ranging from less than 9 to less than 12 to define remission (Forlenza et al, 2001;Schweitzer et al, 2001). Thus, the cut-off of less than 10 in the present study seems reasonable.…”
Section: Discussionmentioning
confidence: 74%
“…This study aimed to examine remission based on a categorical MADRS score less than ten. Other studies have used MADRS scores ranging from less than 9 to less than 12 to define remission (Forlenza et al, 2001;Schweitzer et al, 2001). Thus, the cut-off of less than 10 in the present study seems reasonable.…”
Section: Discussionmentioning
confidence: 74%
“…We were able to find the vast majority of studies identified as unpublished in previous reviews (Bondareff et al, 2000;Branconnier et al, 1982;Forlenza et al, 2001;Guelfi et al, 1999;Hoyberg et al, 1996;Katona et al, 1998;Newhouse et al, 2000;Roose et al, 2004;Schatzberg and Roose, 2006;Schatzberg et al, 2002;Smeraldi et al, 1998;Trick et al, 2004;Wehmeier et al, 2005).…”
Section: Resultsmentioning
confidence: 81%
“…In the 16 RCTs that used our primary outcome criterion of remission, no significant difference could be demonstrated between treatment with a TCA compared neither with SSRIs (five RCTs; Forlenza et al, 2001;Guillibert et al, 1989;Kyle et al, 1998;Limosin et al, 2006;Wehmeier et al, 2005) nor with other antidepressants (7 RCTs; Georgotas et al, 1986; Gerner et al, 1980;Kok et al, 2007;Nair et al, 1995;Tignol et al, 1998;Trick et al, 2004;Waite et al, 1986), nor between SSRIs compared with other antidepressants (four RCTs; Falk et al, 1989;Karlsson et al, 2000;Schatzberg and Roose, 2006;Schatzberg et al, 2002) (Fig. 4).…”
Section: Different Efficacy Between Classes Of Antidepressantsmentioning
confidence: 96%
See 1 more Smart Citation
“…The aim of the present study is to evaluate the effect of short-and long-term antidepressant treatment with sertraline on the expression of total and phosphorylated GSK3B in platelets of patients with latelife major depression. Sertraline was chosen in this study because it is widely used as a safe and effective drug for the treatment of major depression in the elderly (Forlenza et al, 2001). Moreover, it has been shown to improve cognitive performance in these patients (Devanand et al, 2003).…”
Section: Introductionmentioning
confidence: 99%